The participation of nongovernmental organizations in poverty alleviation a case study of the Honduras Social Investment Fund Project - Webb, Anna Kathryn Vandever; Sant'Anna, Anna M.; Lee, Kye Woo (World Bank discussion papers, 1995)
"Analyzes how relative strengths and resources of NGOs and the public sector may complement each other to offer services more effectively. After highlighting typical problems, authors offer recommendations for improving collaboration among governmental and implementing agencies, NGOs, and the World Bank"--Handbook of Latin American Studies, v. 57